High Resolution Attenuation Images From Active Seismic Data: The Case Study of Solfatara Volcano (Southern Italy) - De Landro, Grazia; Serlenga, Vincenzo; Amoroso, Ortensia; Russo, Guido; Festa, Gaetano; Zollo, Aldo (Frontiers in Earth Science, 2019)
The quality factor Q is highly sensitive to the medium properties related to the fluid presence, like porosity, permeability, and level of rock saturation. Therefore, it is very useful to image the subsoil of volcanoes in terms of anelastic images, in addition to more common elastic tomographic models. In this setting, indeed, fluids play a key role in controlling and governing the evolution of magmatic processes, so their accurate identification and tracking is crucial. Here, we describe a methodology that allows to obtain accurate 1-D and 3-D attenuation models from seismic active data. This methodology requires three steps: 1/the measurement of the attenuation parameter t∗, first by cross-correlating the signal with the known source function and then by using the spectral decay method; 2/the determination of a reference 1-D attenuation model through a grid model search procedure; 3/the reconstruction of the 3-D attenuation model through an iterative inversion of t∗ data. The map of t∗ residuals can be analyzed with respect to the reference 1-D model in order to validate the t∗ catalog. The methodology has been tested on a small-scale volcanic volume of the shallow Solfatara crater, in southern Italy, as for this area several multi-parametric geophysical surveys have been carried on. The shallowest subsoil of Solfatara is characterized as a volume with a very low P-wave quality factor (QP 5–40 in the near-surface layer 30 m thick), which globally increases with depth in the explored volume and shows a strong lateral heterogeneity. Within the well resolved central portion of the explored volume the QP model shows features consistent with the hydrothermal fluid distribution within Solfatara, inferred by the velocity images. The presented methodology can be therefore considered as a suitable tool to obtain attenuation models in volcanic areas, which, interpreted jointly with the velocity ones, provide a comprehensive image of complex hydrothermal systems.